2005
DOI: 10.1007/s00520-005-0849-9
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine in cancer pain

Abstract: Buprenorphine is a broad spectrum, highly lipophilic, and long-acting partial mu opioid receptor agonist that is noncross tolerant to other opioids. Buprenorphine can be given by several routes. Metabolism is through CYP3A4 and CYP2C8 and by conjugases. Constipation and sexual dysfunction appear to be less with buprenorphine than with other opioids. The recent development of a polymer matrix patch delivery system for buprenorphine prevents "dose dumping" and facilitates pain management in those unable to take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 73 publications
0
60
0
Order By: Relevance
“…New evidence on the pharmacology of BUP [4,5,6,8,13] availability of a transdermal formulation (TD-BUP) have offered an opportunity to expand the utility of this drug in the context of the management of cancer-related pain.…”
Section: Introductionmentioning
confidence: 99%
“…New evidence on the pharmacology of BUP [4,5,6,8,13] availability of a transdermal formulation (TD-BUP) have offered an opportunity to expand the utility of this drug in the context of the management of cancer-related pain.…”
Section: Introductionmentioning
confidence: 99%
“…Buprenorphine appears to have little analgesic cross-tolerance to other opioids [31]. Sublingual and parenteral formulations are available in the United States and a transdermal matrix patch in Europe [32,33].…”
Section: Buprenorphinementioning
confidence: 99%
“…Drug interactions are rare because the rate-limiting step is glucuronidation for both the parent drug and the major active metabolite norbuprenorphine. In addition, unlike fentanyl, buprenorphine is safe in renal failure [31]. Further research, however, is necessary in the use of buprenorphine in neuropathic pain which should be compared to other potent mu receptor agonists and tramadol.…”
Section: Buprenorphinementioning
confidence: 99%
“…Recent experimental studies have confirmed that no refractory period between the offset of action BUP and the onset of action of other opioids mu-agonists exists. The persistent receptor occupancy has been seen in isolated receptor preparation, while under in vivo conditions the accessibility of mu-receptor sites is maintained [1,2]. Experiences in cancer pain management showed that patients who switched from other opioids encountered no problems with the conversion [3,5].…”
mentioning
confidence: 95%